2022
DOI: 10.3389/fphar.2021.724439
|View full text |Cite
|
Sign up to set email alerts
|

The Potency of Moringa oleifera Lam. as Protective Agent in Cardiac Damage and Vascular Dysfunction

Abstract: Cardiac damage and vascular dysfunction due to underlying diseases, such as hypertension and cardiac thrombosis, or side effects from certain drugs may lead to critical illness conditions and even death. The phytochemical compounds in natural products are being prospected to protect the heart and vascular system from further damage. Moringa genus is a subtropical tree native to Asia and Africa, which includes 13 species; Moringa oleifera Lam. (MO) is the most cultivated for its beneficial uses. MO is also know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 102 publications
0
24
0
Order By: Relevance
“…Moringa oleifera Lam (MOL) contains many bioactive and antioxidants materials which may overcome oxidative stress and degenerating diseases [ 11 , 12 ]. Moringa oleifera Lam leaves have many biological activities that can be used in the prevention of cardiovascular diseases [ 13 ], such as immune boosting agent and hypotension [ 14 ], cholesterol lowering, diuretic and antiulcer properties [ 15 ] and antioxidant activity [ 16 ]. These properties are mostly useful for protecting the liver against hepatotoxin-induced toxicity [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moringa oleifera Lam (MOL) contains many bioactive and antioxidants materials which may overcome oxidative stress and degenerating diseases [ 11 , 12 ]. Moringa oleifera Lam leaves have many biological activities that can be used in the prevention of cardiovascular diseases [ 13 ], such as immune boosting agent and hypotension [ 14 ], cholesterol lowering, diuretic and antiulcer properties [ 15 ] and antioxidant activity [ 16 ]. These properties are mostly useful for protecting the liver against hepatotoxin-induced toxicity [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have shown that Vinco has anti-inflammatory activities in vivo and anti-proliferative effects in vitro [1,7,[24][25][26]; and Vinco also has cytotoxic, anthelmintic, analgesic, anti-bactericidal activities [2,[27][28][29] and with potential therapeutic effects on type 2 diabetes [30]. Evidence indicated Vinco as protective agent in cardiac damage and vascular dysfunction [31]. Some investigations over the past three decades have indicated that Vinco inhibited the proliferation of cancer cells and promoted their apoptosis [3,5], and that it antagonized cardiotoxicity that induced by doxorubicin in rats in vitro and in vivo [10,31].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence indicated Vinco as protective agent in cardiac damage and vascular dysfunction [ 31 ]. Some investigations over the past three decades have indicated that Vinco inhibited the proliferation of cancer cells and promoted their apoptosis [ 3 , 5 ], and that it antagonized cardiotoxicity that induced by doxorubicin in rats in vitro and in vivo [ 10 , 31 ]. These evidences indicated that Vinco played a complex role in regulating anti-inflammatory and anti-bacterial activities and antagonizing cardiotoxicity; it also has a capacity to inhibit the growth of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Within a short period, GR was rapidly distributed to tissue with high blood flow, such as the spleen, heart and kidney. A very slight amount was distributed to brain, liver, and lung implying that the distribution may be influenced by the perfusion rate of the organs ( Li et al, 2019b ; Alia et al, 2022 ). Additionally, the presence of GR in the brain tissue demonstrates its potential to cross the BBB.…”
Section: Pharmacokinetics Of M Oleiferamentioning
confidence: 99%
“…The LD 50 of ethanol extract was 39,600 mg/kg, and the aqueous extract at 16,100 mg/kg, which was within the safe range ( Kasolo et al, 2012 ). An evaluation of sub-acute toxicity on Swiss albino rats revealed that ethanol solvent was safer as compared to aqueous ( Alia et al, 2022 ). Sub-acute administration of M. oleifera aqueous extracts at 16,100 mg/kg demonstrated mild signs of organ toxicity, such as an increase in the concentrations of white blood cells, potassium ions (K + ), chloride ions (Cl − ), and calcium ions (Ca 2+ ) and a rise in alkaline phosphatase, aspartate aminotransferase, total bilirubin, and alanine aminotransferase.…”
Section: Safety and Toxicology Assessment Of M Oleiferamentioning
confidence: 99%